Effect of soils on formation of active compounds on Brassica napus L. which grow in Iraq - Fathi A. Al-Mandeel; Abdulmoneim M.A.Kannah (Tikrit Journal of Pure Science)
In this study, phenolic compounds : Hydroquinone, Resorcinol, Salicylic acid, Vanillin and Gallic acid. were separated from crude of Herbs belonging to Brassica napus that were collected from four sites, three of which are located within the city of Mosul are : Al-Rashidiya (area used for the cultivation of crops) and Shalalat Al-Mosul (Mosul Niagara, tourist area) and the campus of the Mosul University, while the fourth site is located in the rural of Mosul, at the village of Abukudoor, about 35 kilometers west of the Mosul city.